2000
DOI: 10.1104/pp.122.2.505
|View full text |Cite
|
Sign up to set email alerts
|

Redox Control of psbA Gene Expression in the Cyanobacterium Synechocystis PCC 6803. Involvement of the Cytochrome b6/fComplex

Abstract: We investigated the role of the redox state of the photosynthetic and respiratory electron transport chains on the regulation of psbA expression in Synechocystis PCC 6803. Different means to modify the redox state of the electron carriers were used: (a) dark to oxidize the whole electron transport chain; (b) a shift from dark to light to induce its reduction; (c) the chemical interruption of the electron flow at different points to change the redox state of specific electron carriers; and (d) the presence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…In contrast, Glc expression of group II genes was abolished by the electron transport inhibitor Hg 21 or CN 2 , which would maintain the PQ pool in an oxidized or a reduced state, respectively, indicating the involvement of decreased cytosolic NADPH content rather than changes in membrane redox state in group II gene expression. If membrane redox were involved, then differential effects of Hg 21 and CN 2 would be expected; for instance, if the redox state of the PQ is critical, as has been shown for the expression of photosynthesis-related (Alfonso et al, 2000;Li and Sherman, 2000) and RNA synthesisrelated genes (Kujat and Owttrim, 2000), Hg 21 treatment Figure 5. Effects of respiration inhibitors (6-AN, Hg 21 , and CN 2 ) and an uncoupler (CCCP) on Glc-induced accumulation of respiratory gene transcripts in the dark.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Glc expression of group II genes was abolished by the electron transport inhibitor Hg 21 or CN 2 , which would maintain the PQ pool in an oxidized or a reduced state, respectively, indicating the involvement of decreased cytosolic NADPH content rather than changes in membrane redox state in group II gene expression. If membrane redox were involved, then differential effects of Hg 21 and CN 2 would be expected; for instance, if the redox state of the PQ is critical, as has been shown for the expression of photosynthesis-related (Alfonso et al, 2000;Li and Sherman, 2000) and RNA synthesisrelated genes (Kujat and Owttrim, 2000), Hg 21 treatment Figure 5. Effects of respiration inhibitors (6-AN, Hg 21 , and CN 2 ) and an uncoupler (CCCP) on Glc-induced accumulation of respiratory gene transcripts in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…These results also rule out the possibility that the Glc transporter (or homologs) and the glucokinase have regulatory roles as they do in higher plants and yeast (Rolland et al, 2002). During respiration, changes in the cellular redox state [NAD(P)H to NAD(P) 1 ratio], the redox state of respiratory electron transport, cytosolic pH, and energy charge in terms of the ATP to ADP ratio occur sequentially, resulting in the transcriptional regulation of genes encoding enzymes involved in respiratory electron transport in Streptomyces coelicolor A3(2) (Brekasis and Paget, 2003), photosynthesis (Alfonso et al, 2000;Li and Sherman, 2000), RNA synthesis (Kujat and Owttrim, 2000), and pigment biosynthesis (Ryu et al, 2004) in Synechocystis, and Glc repression in yeast (Rolland et al, 2002). By analogy, these changes could be candidate signals for the Glc-induced expression of the respiratory genes observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in chloroplasts, the transcription of many cyanobacterial photosynthesis genes is influenced by light and photosynthetic electron transport [37][38][39]. Under photoautotrophic conditions, DCMU and DBMIB can be used to manipulate the redox state of the PQ pool in the same way as in chloroplasts [40,41]. Furthermore, the sequencing of the Arabidopsis genome revealed that many genes of cyanobacterial origin have been maintained throughout evolution, suggesting that, at least in part, its gene products could still have their former function [42].…”
Section: Redox Signalling Pathways In Cyanobacteria -A Model For Chlomentioning
confidence: 99%
“…S2). The lower pigment content observed under HL might lead to a lower redox state of the electron transport chain (Alfonso et al, 2000), which might be a strategy to avoid the production of reactive oxygen species and the inhibition of photosynthesis (Hihara et al, 2001;Muramatsu et al, 2009), particularly when photoassimilates cannot be used for cell division. Interestingly, Kopecná et al (2012) showed that, even with a lower cellular chlorophyll content under HL, the rate of chlorophyll synthesis was higher than at lower light intensity.…”
Section: Metabolic and Physiological Traits During The Stationary Phasementioning
confidence: 99%